Effects of Husk Ash Dosage and Leaf Fertilizer Concentration on the Growth and Results of Celery Plants (Apium graveolens) - Ayu Puspita; Tri Pamujiasih; Libria Widiastuti (JURNAL ILMIAH AGRINECA, 2022)
This research was conducted to determine the dose of husk ash and concentration of POC Nasa leaf fertilizer on the growth and yield of celery plants. This research has been carried out from August 2021 to November 2021, in Karangasem Village, Kel. Sraten, Kac. Gatak, Kab. Sukoharjo with an altitude of 129 m above sea level. This study used the factorial method with a completely randomized design (CRD) pattern consisting of two treatment factors. The treatment factor was the administration of husk ash dose A (A? = without husk ash, A? = 40 grams, A? = 50 grams). Concentration of foliar fertilizer POC Nasa P (P? = without POC Nasa, P? = 2 cc/ltr, P? = 3 cc/ltr). The data obtained were analyzed with 5% variance if it had a significant effect, then it was continued with the 5% DMRT test. The results showed that the administration of a combination treatment of husk ash dose and concentration of POC Nasa (AxP) leaf fertilizer was significantly different to the number of leaves per strand. The treatments of various doses of husk ash were not significantly different to the six observation parameters and the concentration treatment of POC Nasa leaf fertilizer was not significantly different to the six observation parameters. The highest number of plant leaves 78 g was obtained in the combination of A?P? (husk ash 50 g and concentration of POC Nasa leaf fertilizer 2cc/?). The lowest number of plant leaves 22 g was obtained in the combination of A?P? (Husk Ash 50 g and concentration of POC Nasa Leaf Fertilizer 3cc/?).